A Novel Approach of Renewable Energy Powered Hybrid Electrical Vehicle Using BLDC Motor - Rao, Ch. UmaMaheshwar; Suresh, K.; Reddy, A. Naveen (International Journal of Engineering and Technology, 2018)
Renewable energy based hybrid electrical vehicle (HEV) has been useful to make clean and green environment. Solar energy is available during day time which feed energy to run HEV and opposite wind energy also one of the input and it also useful to feed energy input to the vehicle. In the existing system of hybrid powered vehicles are not utilizing this energy properly due to some drawbacks related to blade stiffness, vehicle friction torque and efficiency. This proposed system overcome those difficulties and supply the power very conveniently. The noveltyof this paper is wind extraction; this system of approach is very helpful to convert the available opposite wind to the vehicle into useful energy. Wind outlet provisions are also available to reduce vehicle friction torque. The power sources such as solar, wind and fuel cell and the appliances of the car made sophisticated, which are controlled by a universal controller. The BLDC motor controlled by fuzzy PID concept of making the system is so reliable and control all the system operations effectively.